Distribution and conservation status of Scutellaria rupestris subsp. cephalonica (Rech.f.) Greuter & Burdet - Gerakis, Argyrios; Frangos, Athanasios; Haldas, Xenophon; Katsalirou, Eirini; Samaras, Yiannis (Hacquetia, 2023)
Scutellaria rupestris subsp. cephalonica (Rech.f.) Greuter & Burdet (Lamiaceae) is a perennial herb endemic to Mounts Ainos and Roudi on the island of Cephalonia. Until now, information about the taxon’s distribution has been sketchy: two fairly localized populations on Mt. Ainos have been reported, one of them extinct, and two on Mt. Roudi, without specifics. Because we thought that the taxon is much more common, we designed a survey along contours encircling the two peaks totaling 80 km. We recorded 112 locations of the taxon. We found that S. rupestris subsp. cephalonica prefers sunny clearings within fir forest as well as crevices among limestone rock on somewhat flat terrain. On Mt. Roudi, the taxon grows above 800 m, and is rather uncommon. On Mt. Ainos, the taxon is quite common above 1100 m; below that altitude it has not been confirmed. The findings were more abundant on the NE slope of Mt. Ainos which is wetter and possibly cooler than the SW slope due to being shaded and more forested, less eroded, and with a deep organic layer. The main threat to the survival of the taxon is illegal grazing. The proposed Red List assessment according to IUCN is EN B1ab(iii)+2ab(iii).